PELATIHAN HANTARAN DALAM UPAYA MEMBENTUK WARGA BELAJAR YANG BERDAYA - Nandang Rukanda; Agus Hasbi Noor (IKIP SILIWANGI, 2020)
The Objectives of Community Service These are (1) To register the existence of a Community Learning Center for Community Activities (PKBM) in Purwakarta Regency. (2) To find out the conduct of delivery training in PKBM learning residents in Purwakarta Regency, and (3) To find out the understanding mastery of mastery skills for PKBM learning residents in Purwakarta Regency. The scientific references used in this community service are training, participatory training, training, and training results. Location of Community Service is carried out in Purwakarta Regency for residents learning PKBM. The population released 20 people, who were taken from the residents studying PKBM in Purwakarta, while the sample used Non-Probability Sampling. Dedication Method by doing direct fielding through field training. The following steps are issued in this dedication are (1) Preliminary study (2) Literature study (3) Compiling service plan (4) Making observation and interview guidelines (5) Analysis of results and (6) Making reports. The results of community service on training to make intermediaries help improve independence and empowerment for citizens to learn PKBM. Changes in learning citizens' knowledge can be seen in their knowledge, attitudes, and skills. The impact in the field makes it possible for citizens to learn to become entrepreneurs and stimulated communities to become independent communities.